2018
DOI: 10.2147/copd.s147718
|View full text |Cite
|
Sign up to set email alerts
|

Case-finding for COPD in primary care: a qualitative study of patients’ perspectives

Abstract: BackgroundCOPD is a leading cause of morbidity and mortality, yet it remains largely under-diagnosed. Case-finding is encouraged by many professionals, but there is a lack of information on the patients’ views and perspectives.Patients and methodsSemistructured interviews were conducted with adults, aged 40 years or older with a history of smoking, who were eligible and invited for case-finding for COPD as a part of a large UK primary care trial. Patients, including those who consented or declined participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
3
17
0
1
Order By: Relevance
“…Possible reasons for the low response rate in our research may be due to denial of symptoms particularly if the symptoms are mild and not limiting daily activities. People may also avoid addressing their lung health due to the potential stigma of having a chronic lung disease caused by their tobacco dependency 42 , 43 . Potential cost implications such as an increase in life and travel insurance, as well as the cost of prescriptions may also be a factor to decline participation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for the low response rate in our research may be due to denial of symptoms particularly if the symptoms are mild and not limiting daily activities. People may also avoid addressing their lung health due to the potential stigma of having a chronic lung disease caused by their tobacco dependency 42 , 43 . Potential cost implications such as an increase in life and travel insurance, as well as the cost of prescriptions may also be a factor to decline participation 44 .…”
Section: Discussionmentioning
confidence: 99%
“… 18 A qualitative study with patients also found that GPs often lack the time to engage in case finding, that accessing primary care appointments can be difficult, and that communication about a diagnosis can often be lacking. 19 In addition, patients may occasionally be in denial of their respiratory symptoms or may not prioritise this over other health issues. Case finding strategies will therefore need to address patient education on accessing health services more promptly for respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Két interjúalany visszakapcsol az orvosi kommunikációhoz: az orvos küldjön pozitív visszajelzést, ha ezek bármelyike megtörtént, "ünnepelje a beteget". Az esélyadás kétoldalú: ha a beteg elfogadja a betegségét, és elhiszi, hogy az inhalátor tud neki segíteni, akkor ez már az első lépés a gyógyulás felé vezető úton [21]. A rehabilitációban való részvétel és az eredmények mindennapokba ültetése pedig megalapozza ennek a hosszú távú sikerét [22].…”
Section: Az Oktatóprogram Szempontjaiunclassified